Mechanisms of L-DOPA-induced dyskinesia in Parkinson's disease - Cenci, Angela (Henry Stewart Talks, 2014)
Characteristics of Parkinson´s disease (PD), Dysregulation of dopamine release and re-uptake in the striatum, L-DOPA as a drug for PD, L-DOPA-induced dyskinesia (LID), Pre- and post-synaptic mechanisms of LID, Serotonin neurons, dopamine and LID, Genes linked to involuntary movements (ΔFosB, ERK1/2, mGluR5), Spiny projection neurons (SPNs) in PD and LID